2007
DOI: 10.1016/j.icarus.2006.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Circular polarization in comets: Observations of Comet C/1999 S4 (LINEAR) and tentative interpretation

Abstract: Comet C/1999 S4 (LINEAR) was exceptional in many respects. Its nucleus underwent multiple fragmentations culminating in the complete disruption around July 20, 2000. We present circular polarization measurements along the cuts through the coma and nucleus of the comet during three separate observing runs, in June 28-July 2, July 8-9, and July 21-22, 2000. The circular polarization was detected at a rather high level, up to 0.8%. The left-handed as well as right-handed polarization was observed over the coma wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 69 publications
(97 reference statements)
3
26
0
Order By: Relevance
“…5) had the goal to test whether optically active, possibly organic surface material is present on the bright hemisphere that is believed to induce circular polarization of a few percent due to its chiralic character (Sterzik et al 2010, Rosenbush et al 2007). Our observed circular polarization depends on the instrument position angle, and in particular it changes in sign when the instrument is rotated by 90…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5) had the goal to test whether optically active, possibly organic surface material is present on the bright hemisphere that is believed to induce circular polarization of a few percent due to its chiralic character (Sterzik et al 2010, Rosenbush et al 2007). Our observed circular polarization depends on the instrument position angle, and in particular it changes in sign when the instrument is rotated by 90…”
Section: Discussionmentioning
confidence: 99%
“…To confirm the notion of Rosenbush et al (2002) that Iapetus' bright hemisphere displays two branches of negative polarization, one called the polarization opposition effect (occurring at very small phase angles), and the other one called the normal branch of negative polarization (at relatively higher phase angles), measurements at low phase angles would be highly needed. Apart from being a test for optically active (chiral) organic molecules, circular polarization is also believed to be sensitive to the shape, structure and composition of the scattering surfaces (Rosenbush et al 2007), and thus, our measurement of circular polarization of Iapetus' bright hemisphere combined with its linear polarization measurements would allow one to translate this polarimetric characteristic of typical water ice to the light scattering behaviour of other solar system bodies of dominant water ice surface constitution.…”
Section: Discussionmentioning
confidence: 99%
“…It is already known that chirality is not a purely terrestrial phenomenon; excesses in left-handed amino acids have been found in meteorites (Cronin and Pizzarello, 1997;Pizzarello and Cronin, 2000). It has also been suggested that homochirality may explain circular polarization observed in comets (Rosenbush et al, 2007(Rosenbush et al, , 2008. Although the origin of homochirality is still not determined, there is evidence that it may be connected to early stages of the development of planetary systems, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…We simulated results of the observations considering light-scattering by particles whose material contained some excess of chiral organics, and, as a result, possessed some optical 312 Vera K. Rosenbush et al (Rosenbush, Shakhovskoy & Rosenbush 1997, Manset & Bastien 1997, D/1999 S4 (LINEAR) (Rosenbush et al 2007b), C/2001 Q4 (NEAT) (Rosenbush et al 2007a), and 73P/Schwassmann-Wachmann 3 (Tozzi et al 2006). The solid line is the linear fit to the observed data, dashed line represents results of our calculations for optically active (chiral) spherical particles.…”
mentioning
confidence: 99%
“…The solid line is the linear fit to the observed data, dashed line represents results of our calculations for optically active (chiral) spherical particles. activity (for details see Rosenbush et al 2007b). The simulations were done using the theoretical solution for optically active spheres (Bohren & Huffman 1983).…”
mentioning
confidence: 99%